STUDY OF THE JOINT EFFECT OF MILLIMETER RANGE ELECTROMAGNETIC IRRADIATION AND CADMIUM IONS ON MALONIC DIALDEHYDE CONCENTRATION AND CATALASE ACTIVITY IN WHEAT SEEDLING CELLS (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
In the work the joint effect of millimeter range electromagnetic waves and heavy metal cadmium ions on the intensity of lipid peroxide oxidation and catalase activity in wheat seedling cells has been studied. The obtained data were compared with the results received at separate influence of each of these factors. It was shown that the joint effect of electromagnetic waves and heavy metal results in improving of criteria of free-radical processes and antioxidant system activation. It was also shown that acting separately the aforementioned factors lead to sharp changes of these criteria.
Keywords: wheat seedling, irradiation, heavy metal effect, malonic dialdehyde content, catalase activity